2021
DOI: 10.3390/ph14030193
|View full text |Cite
|
Sign up to set email alerts
|

RETRACTED: Qian et al. Sanguinarine Inhibits Mono- and Dual-Species Biofilm Formation by Candida albicans and Staphylococcus aureus and Induces Mature Hypha Transition of C. albicans. Pharmaceuticals 2020, 13, 13

Abstract: The journal retracts the article [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Unlike those studies, we confirmed a potential antifungal activity of SAN against C. albicans clinical isolates. In line with the previously observed antibiofilm effects of SAN (Zhong et al, 2017 ; Qian et al, 2021 ), SAN caused obvious morphological changes in planktonic cells, including cell disruption and changes to the alignment of plasma membranes ( Figure 2 ), demonstrating for the first time that SAN may lead to cell membrane damage. Our results demonstrated that the treatment of C. albicans cells with SAN resulted in significant modifications in the cell wall and membrane, as examined by SEM and TEM.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike those studies, we confirmed a potential antifungal activity of SAN against C. albicans clinical isolates. In line with the previously observed antibiofilm effects of SAN (Zhong et al, 2017 ; Qian et al, 2021 ), SAN caused obvious morphological changes in planktonic cells, including cell disruption and changes to the alignment of plasma membranes ( Figure 2 ), demonstrating for the first time that SAN may lead to cell membrane damage. Our results demonstrated that the treatment of C. albicans cells with SAN resulted in significant modifications in the cell wall and membrane, as examined by SEM and TEM.…”
Section: Discussionsupporting
confidence: 90%